Cardiovascular and metabolic problems associated with application of second generation tyrosine kinase inhibitors in patients with chronic myeloid leukemia - O. Y. Vinogradova (Онкогематология, 2015)
During therapy with second generation tyrosine kinase inhibitors in patients with chronic myeloid leukemia, a number of patients demonstrate non-hematological toxicity of various degrees. The article contains review of references about second generation tyrosine kinase inhibitors effect on the frequency of cardiovascular and metabolic problems.